Solar Prominence - Estes, Dana (Estes & Lauriat, 1872)
Plate from the publication Spectrum Analysis Explained, Including an Explanation of the Received Theory of Sound, Heat, Light, and Color by Dana Estes (1840-1909). The plate depicts Solar prominences as observed by Professor Charles Augustus Young of Dartmouth College on October 7-8, 1869.
Keywords: Spectrum analysis; Sun--Prominences; Young, Charles A. (Charles Augustus), 1834-1908